Design of a Rule-Based Digital Check Ordering Web System at Bank Sumut KCP Binjai - Siregar, Fairuz Azzaria; Salsabila, Salsabila; Putri, Raissa Amanda (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid advancement of digital technology has highlighted the limitations of manual check application and ordering processes, which remain time-consuming, error-prone, and inefficient. Such conditions may hinder the bank’s operational performance and negatively impact service quality for customers. To address these issues, an automated system that simplifies, accelerates, and streamlines check ordering is required. Therefore, this study aims to design a rule-based digital check ordering web system for Bank Sumut KCP Binjai, enabling a faster, more accurate, and well-structured application process. The proposed system automates each step of the check ordering workflow based on predefined rules, including data verification, request processing, and order recording. A rule-based approach ensures consistent operations aligned with standard procedures, reducing reliance on manual tasks and minimizing the risk of human error. Additionally, the system is designed to improve data accuracy, strengthen internal controls, and facilitate efficient information management related to check orders. The main objective of this research is to develop an effective and efficient rule-based web system that supports digital check ordering processes. With the implementation of this system, banking services are expected to become faster, more accurate, and more aligned with sustainable digital transformation efforts, ultimately improving overall customer satisfaction and operational reliability.